Antifibrotic Effects of Kangxian Ruangan Capsule on Rats with Nonalcoholic Fatty Liver Fibrosis and Hepatic Stellate Cells through Regulation of TGF-β and TLR4 Signaling Pathways. (10th August 2021) - Liu, Liming; Zhou, Ying; Dai, Dan; Xia, Hongmei; Zhao, Kang; Zhang, Jianjun
Abstract : Kangxian ruangan (KXRG) is a traditional Chinese medicine (TCM) formula consisting of 12 herbs. TCM syndrome differentiation proposes that KXRG exerts pharmacological effects against nonalcoholic fatty liver disease (NAFLD) fibrosis. This work investigates the effect of KXRG on NAFLD fibrosis in vivo and in vitro . In vivo, the NAFLD fibrosis model was constructed in Wistar rats using methionine- and choline-deficient (MCD) diet, followed by KXRG (0.92 g/kg/d) treatment for 8 weeks. In vitro, primary hepatic stellate cells (HSCs) were activated using platelet-derived growth factor (PDGF) and treated with KXRG. Molecular mechanisms underlying fibrosis were investigated. After 8 weeks, compared with the control groups, the histological lesions, degree of fibrosis, and inflammatory reaction increased with the MCD diet as demonstrated by histological changes and increased fibrosis-related ( α -SMA, TGF- β, COL1A1, and desmin, P < 0.01 ) and inflammation-related factors (TNF- α, MCP-1, and F4/80, P < 0.01 ), whereas they decreased with KXRG treatment (P < 0.01 ). KXRG not only inhibited the proliferation of activated HSCs and promoted their apoptosis but also resulted in G0-G1 arrest. Furthermore, KXRG suppressed HSC activation (P < 0.01 ), collagen synthesis (P < 0.01 ), and α -SMA expression (P < 0.01 ) with PDGF stimulation. In both the MCD diet-induced animal model and PDGF-induced cell model, KXRG inhibited TGF- β and TLR4 signaling (P < 0.01 ), similar to corresponding small-molecule inhibitors. These results demonstrated that KXRG might exert suppressive effects against NAFLD fibrosis via regulating TGF- β and TLR4 signaling. KXRG may act as a natural and potent therapeutic agent against NAFLD.